Identyfikacja osi w skalowaniu wielowymiarowym na przykładzie segmentacji rynku ubezpieczeniowego - Batóg, Barbara; Wawrzyniak, Katarzyna (Identification of axis in multidimensional scaling for segmentation of insurance market, 2006)
Identification of axis has very great meaning in multidimensional scaling. In literaturę there are presented some methods of doing it. These methods are as follows: analysis of correlation between level of variables and values of dimensions, ProFit analysis, unfolding analysis and Gabriel method. In the paper the authors tried to use all these methods commonly in order to achieve better identification of axis in case of segmentation of insurance market on the base of individual preferences of client and non-clients connected with insurance products and services.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (13); 2006; nr 1126, s. 372-379